Analysis of Indonesian Mid-Career Diplomats’ Perceptions of International Mutation Through the Lens of Protean Career Orientation - Amisadai, Yuvi Shandy; Andrias, Mone Stepanus (AFEBI Management and Business Review, 2024)
This study explores how Indonesian mid-career diplomats perceive international mutations, defined as assignments to diplomatic missions abroad. Using a protean career orientation lens, we investigate how financial security, personal development, and internal factors like family influence their decisions. Through thematic analysis of interviews with nine mid-career diplomats, we uncover a dissonance between their career aspirations and the current mutation system. Findings suggest that the Ministry of Foreign Affairs could benefit from incorporating diplomats' goals while ensuring organizational needs are met. This research contributes to understanding career management in diplomatic services and underscores the need for a more employee-centric approach to international mutations.